Tratamiento de los trastornos venosos del miembro superior - Czarnevicz, Daniel; Navarro, Teodoro; Baldizán, Jorge; Danza, Rómulo (Cirugía del Uruguay, 1991)
The incidence of venous thrombosis of the upper limbs rises daily because of the growing usage of invasive techniques. Other etiologies are a/so ana/ysed. A brief analysis of treatment with heparin and fibrinolytics is made. Surgical indication is reserved only far cases where medica/ treatment fai/s, of in those cases where the postphlebitic syndrome is invalidating.